Credit constraints and investment-cash flow sensitivity in declining economic conditions: The role of reliance on bank debt - Ghada Tayem (Economies, 2022)
This paper examines the sensitivity of investment to cash flow in declining economic conditions, focusing on the impact of a firm's reliance on bank debt. Using the context of Jordan, a developing Middle East and North Africa (MENA) country, the study utilizes the standard Q theory of investment augmented by cash flow, leverage, and liquidity. Then, it allows for differential loading on the cash flow coefficient pre- and post-2008, the year that marks the beginning of declining conditions, and by categorizing companies based on their reliance on bank debt, measured by having access to a bank line of credit. Using alternative estimation specifications, the findings indicate that firms' investments decreased significantly in episodes of declining conditions. In addition, the findings indicate that firms' investments exhibited more sensitivity to cash flow during declining conditions, especially for firms with access to lines of credit. The latter finding suggests that firms reliant on bank debt could not compensate for the credit shortages by switching to other sources of external funding and therefore they were compelled to use more of their internally generated funds to finance their investments.
Keywords: 330; credit constraints; developing markets; economic policy uncertainty; investment-cash flow sensitivity; lines of credit; MENA